Recent Insights Into SREBP as a Direct Mediator of Kidney Fibrosis via Lipid-Independent Pathways - Dorotea, Debra; Koya, Daisuke; Ha, Hunjoo (Frontiers in Pharmacology, 2020)
Sterol regulatory-element binding proteins (SREBPs) are classical regulators of cellular lipid metabolism in the kidney and other tissues. SREBPs are currently recognized as versatile transcription factors involved in a myriad of cellular processes. Meanwhile, SREBPs have been recognized to mediate lipotoxicity, contributing to the progression of kidney diseases. SREBP1 has been shown to bind to the promoter region of TGFβ, a major pro-fibrotic signaling mechanism in the kidney. Conversely, TGFβ activates SREBP1 transcriptional activity suggesting a positive feedback loop of SREBP1 in TGFβ signaling. Public ChIP-seq data revealed numerous non-lipid transcriptional targets of SREBPs that plausibly play roles in progressive kidney disease and fibrosis. This review provides new insights into SREBP as a mediator of kidney fibrosis via lipid-independent pathways.